2014
DOI: 10.3329/jpsb.v1i1.19463
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Surgery: Demand and Survival Both are Increasing: Eight Years Experience in Dhaka Medical College Hospital, Bangladesh

Abstract: :Purpose: In order to achieve the Millennium Development Goal (MDG) 4 target of a two-thirds reduction in under-five mortality from 1990 to 2015, major reductions are going to be required in neonatal mortality. Congenital anomalies have become the fourth cause of neonatal deaths and most of these are curable. Dhaka Medical College Hospital is the largest public hospital of the country and serving the poor and lower middle class people where surgery and medical facilities are mostly free of cost. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…3,8,10,13,16,17 Postoperative mortality in our study was 16% which was in between reported international publications. Hanif et al in their experience in DMCH observed a postoperative mortality of 15.4% and Islam et al reported 20.8% mortality in RMCH which is close to our series.14,18…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…3,8,10,13,16,17 Postoperative mortality in our study was 16% which was in between reported international publications. Hanif et al in their experience in DMCH observed a postoperative mortality of 15.4% and Islam et al reported 20.8% mortality in RMCH which is close to our series.14,18…”
Section: Discussionsupporting
confidence: 77%
“…This male preponderance was also observed in other centres. [11][12][13][14][17][18] In this study, 24 (13%) neonates were preterm (less than 37 completed weeks) and 181 (87%) were full term. Gestational age was variable between 32 and 42 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Anorectal malformation, Intestinal Atresia/ stenosis and Hirschsprungs disease were the commonest diagnoses in this study. These are similar to other reported series 7,16,17 . Preterm birth, LBW, Cesarean delivery and diagnoses like CDH, NEC and EA are significantly associated with in-hospital death of pediatric surgical patients admitted to our NICU.…”
Section: Discussionsupporting
confidence: 93%
“…Otake K et al reported 8.2% death rate among paediatric surgical patients admitted to the NICU 16 . One study in Bangladesh showed 10.61% mortality rate among paediatric surgery patients 17 . More males than females were admitted in our NICU for paediatric surgical diseases as other studies had reported 6,7,[15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation